Christian identity amid Islam in medieval Spain - Tieszen, Charles Lowell, 1978- (Studies on the Children of Abraham, 2013)
In Christian Identity amid Islam in Medieval Spain Charles L. Tieszen explores a small corpus of texts from medieval Spain in an effort to deduce how their authors defined their religious identity in light of Islam, and in turn, how they hoped their readers would distinguish themselves from the Muslims in their midst. It is argued that the use of reflected self-image as a tool for interpreting Christian anti-Muslim polemic allows such texts to be read for the self-image of their authors instead of the image of just those they attacked. As such, polemic becomes a set of borders authors offered to their communities, helping them to successfully navigate inter-religious living.